Refleksi Sufistik dalam Nahwu al-Qulu>b Karya Abu al-Qa>sim Al-Qusyairi> - Maulana, Muhammad Iqbal (IAIN Ponorogo, 2019)
Abstract: The work of al-Qusyairi>, entitled Nah wu al-Qulu> b comprises a discussion of the knowledge of nahwu and Sufism. Al-Qusyairi> was the first scholar which deals with the issue of integrating nahwu and Sufism. The approach of Sufism was employed in composing Nah wu al-Qulu>b. Afterwards, it influences other Sufis to conduct a research dealing with the same subject. Among the Sufis affected by al-Qusyairi> were Ibn Maimu> n, who wrote the book al-Risa> lah al-Maymuniyyah fi Tauh i> d al-Juru> miyyah, Abd Qa> dir bin Ah mad al -Kuha> wrote> Maniyyat al-Faqi> r al-Munjarid wa Sayrat al-Murid al-Mutajarrid, Ibnu 'Aji> bah wrote Khula> s ah Syarh Ibn' Aji> bah 'Ala> Matni al-Juru> miyyah fi al-Tas awwuf, and Kiai Nur Iman Mlangi with his work al-Sani> al-Mat alib. The type of writing occurred due to the emphasis more on Sufism, even though, he is the proficient of Sufism and Tasawuf. In addition, al-Qusyairi>’s work was based on the reason in solving the community problems which has assumption that Tasawuf was considered perverted.الملخص: نحو القلوب هو من تأليفات القصيري الذي يتضمن فيه علم النحوي مع الصوفية. ما فعله قصيري لم يعثر عليه من قبل. كان القصيري أول من بدأ الكتابة. وفقًا للمؤلف، في كتابه